The immunological and structural epidermal barrier dysfunction and skin microbiome in atopic dermatitis-an update - Çetinarslan, Tubanur; Kümper, Lisa; Fölster-Holst, Regina (Frontiers in Molecular Biosciences, 2023)
Atopic dermatitis (AD) is a common, chronic and relapsing inflammatory skin disease with various clinical presentations and combinations of symptoms. The pathophysiology of AD is complex and multifactorial. There are several factors involved in the etiopathogenesis of AD including structural and immunological epidermal barrier defect, imbalance of the skin microbiome, genetic background and environmental factors. Alterations in structural proteins, lipids, proteases, and their inhibitors, lead to the impairment of the stratum corneum which is associated with the increased skin penetration and transepidermal water loss. The elevated serum immunoglobulin E levels and blood eosinophilia have been shown in the majority of AD patients. Type 2 T-helper cell immune pathway with increased expression of interleukin (IL)-4, IL-5, and IL-13, has an important role in the etiopathogenesis of AD. Both T cells and keratinocytes contribute to epidermal barrier impairment in AD via a dynamic interaction of cytokines and chemokines. The skin microbiome is another factor of relevance in the etiopathogenesis of AD. It has been shown that during AD flares, Staphylococcus aureus (S. aureus) colonization increased, while Staphylococcus epidermidis (S. epidermidis) decreased. On the contrary, S. epidermidis and species of Streptococcus, Corynebacterium and Propionibacterium increased during the remision phases. However, it is not clear whether skin dysbiosis is one of the symptoms or one of the causes of AD. There are several therapeutic options, targeting these pathways which play a critical role in the etiopathogenesis of AD. Although topical steroids are the mainstay of the treatment of AD, new biological therapies including IL-4, IL-13, and IL-31 inhibitors, as well as Janus kinase inhibitors (JAKi), increasingly gain more importance with new advances in the therapy of AD. In this review, we summarize the role of immunological and structural epidermal barrier dysfunction, immune abnormalities, impairment of lipids, filaggrin mutation and skin microbiome in the etiopathogenesis of AD, as well as the therapeutic options for AD and their effects on these abnormalities in AD skin.